Highly Stable Ultrathin TiO2 Based Resistive Random Access Memory with Low Operation Voltage. (1st January 2018) - Chen, Shi-Xiang; Chang, Sheng-Po; Chang, Shoou-Jinn; Hsieh, Wei-Kang; Lin, Cheng-Han
Abstract : In this article, we display the fabrication methods and characterizations of the ITO/TiO2 /Pt resistive random access memory (RRAM). By transmission electron microscopy (TEM) analysis, the fabricated TiO2 thin film of our RRAM device was confirmed to be amorphous instead of other common crystal direction. The RRAM here shows bipolar resistive switching characteristic for over a hundred times switching cycles with a resistance ratio (RHRS /RLRS ) of more than 1 order and high stable retention characteristic for over 10 4 seconds with a resistance ratio (RHRS /RLRS ) of around 2 orders. We found that conduction mechanism was dominated only by ohmic conduction in both set and reset procedure. The set and reset voltage of the ITO/amorphous TiO2 (a–TiO2 )/Pt of this article were around 0.6 and –0.5 V, make it state–of–the–art in low operation voltage application.